2020
DOI: 10.1111/ajt.15920
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy maintenance in a kidney transplant recipient with SARS-CoV-2 pneumonia: A case report

Abstract: Am J Transplant. 2020;00:1-3. | 1 amjtransplant.com | INTRODUC TI ONThe novel coronavirus outbreak has startled the world due to its widespread diffusion and socioeconomic burden. Kidney transplant recipients (KTRs) are perceived to be at high risk of infection, and immunosuppressive therapy management during this global emergency can be a challenge. Herein, we report the case of a KTR who developed SARS-CoV-2 pneumonia and recovered in 15 days while continuing administration of his usual immunosuppressive tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 8 publications
0
60
0
5
Order By: Relevance
“…Although renal dysfunction as reflected by decreased eGFR or increased serum levels of creatinine was not considered in the published reports as a co-morbidity, it is important to recognize that renal dysfunction of kidney transplant recipients with COVID-19 ought to be recognized as such. Nevertheless, numerous reports that we reviewed showed that patients with a decreased eGFR plus other comorbidities 39 , 41 , 43 , 44 , 47 , 48 , 52 , 55 or increased serum levels of creatinine plus other comorbidities 36 , 38 , 40 , 42 , 46 , 53 , 54 still achieved a positive outcome. Interestingly, Sharma et al recently completed a retrospective study in which they compared the clinical outcomes of COVID-19 between solid organ transplant recipients and matched nontransplant patients in their medical center, and they found the need for renal replacement therapy in the organ recipients did not affect the incidence of severe COVID-19 and the rate of short-term death 70 .…”
Section: Discussionmentioning
confidence: 91%
“…Although renal dysfunction as reflected by decreased eGFR or increased serum levels of creatinine was not considered in the published reports as a co-morbidity, it is important to recognize that renal dysfunction of kidney transplant recipients with COVID-19 ought to be recognized as such. Nevertheless, numerous reports that we reviewed showed that patients with a decreased eGFR plus other comorbidities 39 , 41 , 43 , 44 , 47 , 48 , 52 , 55 or increased serum levels of creatinine plus other comorbidities 36 , 38 , 40 , 42 , 46 , 53 , 54 still achieved a positive outcome. Interestingly, Sharma et al recently completed a retrospective study in which they compared the clinical outcomes of COVID-19 between solid organ transplant recipients and matched nontransplant patients in their medical center, and they found the need for renal replacement therapy in the organ recipients did not affect the incidence of severe COVID-19 and the rate of short-term death 70 .…”
Section: Discussionmentioning
confidence: 91%
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…There are 39 (97.5%) patients received antiviral therapy (including lopinavir, oseltamivir, arbidol, darunavir, interferon and nitazoxanide) and 32 (80%) patients received hydroxychloroquine [14]. Although most cases received immunosuppression reduction, others studies reported patients with immunosuppression maintained and recovered successfully [27][28][29].…”
Section: Discussionmentioning
confidence: 99%